Ecological correlates of ectoparasite load in a rodent: Complex roles of seasonality. (August 2022) - Shuai, Ling-Ying; Wang, Li-Qing; Wang, Jian-Jun; Xia, Yang; Zhai, Bin-Yan; Xu, Wen-Jie; Chen, Xing-Ming; Yang, Xiao-Yu; Zhang, Fu-Shun
Abstract: Understanding the mechanisms driving parasite distributions is not only important for understanding ecosystem functioning, but also crucial for disease control. Previous studies have documented the important roles of host sex, host body size, host behavioral trait (such as boldness and trappability), and seasonality in shaping parasite load. However, few studies have simultaneously assessed the roles of these factors, as well as their interactions. In spring and summer of 2021, we conducted live trapping in Hohhot, China, to collect ectoparasites on Daurian ground squirrel ( Spermophilus dauricus ), a small rodent widely distributed in East Asian grassland. We then used generalized linear models to explore the effects of several biological factors (sex, body weight, trappability, and reproductive status) and seasonality on the abundance of ticks and fleas in S. dauricus . Significant but inconsistent seasonal effects were observed: tick load was significantly greater in summer than in spring, while flea load was greater in spring than in summer. Seasons also significantly interacted with host trappability and body weight to affect tick abundance. Our results highlight the importance of considering seasonal changes in parasitism, as well as interactions between season and host biological traits in shaping parasite distributions. Graphical abstract: Image 1 Highlights: Both fleas and ticks show seasonal changes in abundance but in different directions. Relationship between host body weight and tick load changes between seasons. Effect of trappability on tick abundance depends on season.